Kirk-Othmer Encyclopedia of Chemical Technology 2003
DOI: 10.1002/0471238961.1921182218050504.a01.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Chlorocarbons and Chlorohydrocarbons, Survey

Abstract: An overview of chlorinated hydrocarbon production is provided. The properties of selected products are discussed, as is the chemistry important to their use and manufacture. Typical manufacturing processes are described. Demand and pricing for the major products are listed, along with the factors influencing consumption trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the study on thermal degradation of chloromethane mixtures [ 15 ], CH 3 Cl was found to be the most thermally stable compound, and CHCl 3 was to be the most thermally labile compound under oxidative and pyrolytic conditions. As listed in Table 1 [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], density, boiling point (b.p. ), viscosity, refractive index, and partition coefficient all increase with increasing chlorine content, while vapor pressure, flammability, dipole (or dielectric constant), water solubility, and latent heat of vaporization at the b.p.…”
Section: Chloromethanesmentioning
confidence: 99%
“…In the study on thermal degradation of chloromethane mixtures [ 15 ], CH 3 Cl was found to be the most thermally stable compound, and CHCl 3 was to be the most thermally labile compound under oxidative and pyrolytic conditions. As listed in Table 1 [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], density, boiling point (b.p. ), viscosity, refractive index, and partition coefficient all increase with increasing chlorine content, while vapor pressure, flammability, dipole (or dielectric constant), water solubility, and latent heat of vaporization at the b.p.…”
Section: Chloromethanesmentioning
confidence: 99%
“…Dangerous volatile compounds such as benzene [ 4 ], 1,3-butadiene [ 5 ], ethylbenzene [ 6 ], xylenes [ 7 ], 1,1,1-trichloroethane [ 8 ], trichloroethylene [ 8 ], tetrachloroethylene [ 9 ], carbontetrachloride [ 10 ], or chloroform [ 11 ] often appear in epidemiological research [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Such compounds often undergo scrutiny from public health institutions, with governments imposing legal limits on their industrial emissions in order to reduce human exposure [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methyl chloride is a versatile methylating agent and as such it is an important intermediate in the chemical industry [1][2][3]. The largest market for methyl chloride is in the production of silicone polymers, which are increasingly applied in traditional nonsilicone applications.…”
Section: Introductionmentioning
confidence: 99%